Glacial Evolution and Paleoclimatic Reconstruction Since the Little Ice Age in the Llanganuco Basin, Cordillera Blanca (Peru) - Iparraguirre Ayala, Joshua Er Addi (2022)
The 58% of Peru's population lives in the arid Pacific coastal region and is highly dependent on the availability of Andean snowmelt water, both for human consumption and for power generation and other economic activities. Tropical glaciers are sensitive indicators of climate change, the impact of which has been reflected in the reduction of glacier areas and volumes. In this paper we present an assessment of the deglaciation and glacial record of temperature increase (°C) in the Llanganuco basin (Cordillera Blanca, Peru) since the end of the Little Ice Age (LIA; ~1850). Deglaciation has been evaluated by reconstructing 2D and 3D glacier surfaces; whereas, the increase in air temperature was deduced from the difference in the Altitude of the Equilibrium Lines in each period analyzed (LIA final, 1962 and 2016). From the Little Ice Age - 1962, the area deglaciated was ~13 km 2 (30% reduction of glacier area; annual retreat= 0.12 km 2 /year). In terms of water volume, it meant a loss of 1358 Mm 3 (a reduction of 51.9% <> 12.1 Mm 3 /year). Between 1962-2016, the area deglaciated was ~7 km 2 (a 23% reduction of glacier area; annual retreat= 0.14 km 2 /year). This meant a water loss of 389 Mm 3 (a reduction of 30.9% <> 7.2 Mm 3 /year). The estimated increase in air temperature was 1.1°C, a coherent value th